B108 From epidural to fascial plane in blunt chest trauma. (11th August 2022) - Singh, A; Howey, S; Egan, T; Verma, P
Abstract : Background and Aims: Following success in thoracic surgery, ultrasound guided fascial plane blocks as effective analgesia for chest wall trauma have increased in popularity over the last decade due to wider patient inclusion and an enhanced safety profile. Fascial plane local anaesthetic can be delivered by continuous infusion or intermittent boluses. Recent evidence promotes programmed intermittent boluses through a peripheral nerve catheter, with a larger volume aiding diffusion, leading to improved pain scores, reduced rescue opioid use and improved patient satisfaction. Royal London Hospital is a MTC; between January 1st2019 and December 1st 2021, 1119 trauma patients were treated with chest injuries. Thoracic epidural analgesia is our current standard analgesia in appropriate chest trauma patients. This requires trained anaesthetic staff, experienced nursing care post-procedure and has an accompanying low but significant complication list. Our project objective is to implement fascial plane chest wall blocks in eligible trauma patients delivered via intermittent programmed boluses to increase the provision of effective analgesia to our trauma cohort. We will record pain scores, rescue analgesic needs and total block duration. Methods: An electronic pump system will deliver a pre-programmed intermittent bolus of 0.125% Levobupivicaine 15 mls every 3 hours alongside a protocolised multimodal analgesic regimen. Results: We hope to demonstrate an increase in fascial plane chest wall blocks at Royal London Hospital and therefore improve our chest trauma care service with the aforementioned benefits of this technique. Conclusions: The reduction in risks associated with insertion and side effects along with minimal contraindications will undeniably transform the care of our trauma patients.